Characteristics of Hydroxypropyl Starch of Sorghum Mutant Line ZH-30 and its Potential use in Paper Industry - S Human; DDS Santosa (Atom Indonesia, 2006)
Sorghum mutant line Zh-30 is a breeding line developed at the Center for the Application of Isotope and Radiation Technology, BATAN by using mutation techniques. Gamma irradiation with the dose of 300 Gy was used to induced plant genetic variability. Through selection processes in several generations, the mutant line Zh-30 was identified to have better agronomic characteristics, better grain quality and higher yield than the original variety. Research on starch quality of this mutant line was done to identify its potential use in a paper industry. Hydroxypropyl starch derivatives of this sorghum lines were prepared by varying alkalinity of the reaction mixtures using propylene oxide to reach Molar of Substitution (MS) of 0–0.180. Its pasting behavior, paste properties and application in wet end paper processing were evaluated. The optimal amount of addition of hydroxypropyl starch was 1-2 %. At this level, drainage time was lower, so that it decreased paper machine speed. At higher level, it did not improve the burst and tensile strengths but tended to decrease the tear strength of handsheets. The properties of lower pasting temperature, higher water holding capacity lower retrogradation susceptibility, increased viscosity and stability of pastes suggested that hydroxypropyl starch of sorghum ZH-30 was suitable for use in wet end paper processing. Comparing to the original starch, the hydroxypropyl starch of sorghum Zh-30 could significantly improve the strength of handsheets.